MEMPELAJARI JANGKA WAKTU BLANSING DENGAN UAP AIR TERHADAP BEBERAPA KARAKTERISTIK TEPUNG TELUR - Dida Riyada (Ma'soem University, 2022)
Egg flour is one form of egg preservation through the process of drying and curing. Besides being more durable, another advantage of egg flour is that the volume of the material becomes much smaller so that it saves storage and transportation space. chemical, quality degradation (Buckle, Edward, Fleet and Wotton, 1987). One of the obstacles in the manufacture of egg flour is the occurrence of the browning process in egg flour. This browning process occurs due to the presence of glucose in the liquid egg which reacts with the amino groups of the protein. The purpose of this study was to determine the appropriate period of blanching with water vapor, in order to obtain some characteristics of good egg flour. The research will be carried out from March to April 2020 in Laboratory Food Technology at the Faculty of Agriculture Ma’soem University, Bandung City. The experimental method used in this study is an experimental method using a Randomized Block Design. Each treatment consisted of 5 treatments and each treatment was repeated 5 times. These factors: blanching period of 1 minute, 3 minutes, 5 minutes, 7 minutes and 9 minutes. The results showed that the blanching period with steam for 3 minutes produced good characteristics. This determination was based on chemical analysis of the water content of egg flour (2.75%), protein content (49.97%) and fat content (35.83%) and organoleptic assessment of color ( 3.40), Aroma (4.30) and Texture of egg flour (2.68)